Écologie des langues dans le Norden - Gadelii, Karl Erland (Nordiques, 2021)
Cet article examine la situation linguistique du Norden du point de vue de l’écologie des langues dans le Nord. Après un aperçu du concept de Norden comme communauté linguistique, la question sera posée de l’idéalisation de cette région, où chaque pays est imaginé comme linguistiquement homogène, et où la communication panscandinave est facilement assurée grâce à une intercompréhension considérable. Cet article met en lumière les conflits linguistiques dans ces régions, particulièrement dans les (ex-)colonies du Danemark et de la Suède. Enfin, il ouvre la réflexion sur les critères qui permettent d’expliquer pourquoi une langue (ex-)coloniale s’impose (tel le suédois au Sápmi) ou non (comme le danois aux îles Féroé). This article examines the linguistic situation in the Nordic countries from the viewpoint of the ecology of languages in the North. Starting out with a presentation of the idea of the Nordic countries as a linguistic community, it then questions the fairly idyllic image of the North where every country is supposed to be linguistically homogeneous, and where pan-Scandinavian communication is guaranteed by an important mutual intelligibility between languages involved. The author rather holds that all Nordic regions host more or less serious linguistic conflicts, in particular the Nordic (ex)colonies, i.e. all Nordic territories except Denmark and Sweden, once colonized by the latter. The article gives an overall picture of linguistic “hegemony” in the Nordic countries, and asks what criteria may decide whether an (ex-)colonial language imposes itself (as in the case of Swedish in Sápmi) or not (see Danish in the Faroe Islands).